The Impact of the Financial and Economic Crisis on Public Private Partnerships - Matej Švigelj; Nevenka Hrovatin (Central European Public Administration Review)
The primary purpose of this paper is to contribute to the current debate on the impact of the economic and financial crisis on public-private partnerships (PPPs). The crisis has caused a substantial fall in the PPP market. PPPs have been exposed to both financial and real impacts of the crisis. High interest rates and limited access to finance have been seen as the main factors reflecting the impact of the financial crisis on PPPs. In addition, due to the recession the decreased revenues of PPP projects have reduced their feasibility or impacted on their overall profitability. Measures adopted to help the PPP market in the analysed countries reveal that they mostly involve some form of government support. Further, the paper also critically examines the deficiencies of PPPs.